2010
DOI: 10.1634/theoncologist.2010-0044
|View full text |Cite
|
Sign up to set email alerts
|

Age and Axillary Lymph Node Ratio in Postmenopausal Women with T1-T2 Node Positive Breast Cancer

Abstract: After completing this course, the reader will be able to:1. Identify changes in medical/surgical practice that can affect the prognostic performance of established prognostic factors such as lymph node involvement in breast cancer.2. Explain how the lymph node ratio can help to adjust against practice-related changes.3. Use the lymph node ratio as a measure of tumor burden in order to weigh the risk of breast cancer death against other causes of death in elderly patients.This article is available for continuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…[14] The SEER set has been widely used for the analysis of LNR staging of breast, colon, gastric and other cancers. [11], [15], [16].…”
Section: Methodsmentioning
confidence: 99%
“…[14] The SEER set has been widely used for the analysis of LNR staging of breast, colon, gastric and other cancers. [11], [15], [16].…”
Section: Methodsmentioning
confidence: 99%
“…Patients were excluded as the follow criteria: (a) obtained neoadjuvant chemotherapy before operation, (b) the total excision lymph nodes less than 10 (Singletary et al, 2002;Vinh-Hung et al, 2009), and bilateral BC (Vinh-Hung et al, 2010). Two hundred and ninety four BC patients with lymph nodes positive were enrolled with 116 cases from Group A, and 178 cases from Group B.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…They concluded that oncologist can be confident that prognosis and decisions on adjuvant therapies can be based on pN classification alone when adequate axillary dissections are performed (>15 nodes) but suggest that pN and LNR should be used on conjunction otherwise [2]. In our study, the mean number of axillary lymph nodes that were examined was [15], which could account for non-significance of our findings.…”
Section: Discussionmentioning
confidence: 59%
“…The LNR was calculated as the total number of positive lymph nodes divided by the total number of lymph nodes found and examined. The cohort was then divided into 3 groups based on established LNR cut-offs [4,12,15,16,21] defined as low risk, 0.01-0.20; intermediate-risk, 0.21-0.65; and high-risk, >0.65. We examined the prognostic value of Lymph Node Ration (LNR) for patients with node-positive breast cancer with varying numbers of minimum nodes removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation